A global Unified Dosimetry Index (gUDI) to evaluate simultaneous integrated boost radiotherapy plans in prostate cancer. Issue 2 (August 2018) - Mambretti, Maddalena; Romanò, Chiara; Marvaso, Giulia; Comi, Stefania; Cambria, Raffaella; Ciardo, Delia; Emiro, Francesca; Fodor, Cristiana; Zerini, Dario; Riva, Giulia; Petralia, Giuseppe; De Cobelli, Ottavio; et al.
Abstract: Purpose: Formulation of a global Unified Dosimetry Index (gUDI) for the evaluation of prostate simultaneous integrated boost Volumetric Modulated Arc Therapy (VMAT by RapidArc) radiotherapy plans. Methods and materials: Dose coverage, conformity, homogeneity and dose gradient index could be included in the Unified Dosimetry Index (UDI). We developed a global UDI to evaluate treatment plans containing volumes irradiated with different dose prescriptions: Intensity Modulated Radiation Therapy with simultaneous integrated boost (IMRT-SIB) with 2 dose levels (36.25 Gy/5 fz for the whole prostate gland and 37.5 Gy/5 fz for Dominant Intraprostatic Lesion (DIL)). To validate gUDI scoring system, 65 prostate cancer patients were evaluated. Mean ( µ ) and standard deviations ( σ ) were calculated for all dosimetry indices and gUDI. Furthermore, gUDI µ and σ were analyzed to compare and classify treatment plans: plans can be ranked as "excellent", "good", "average" or "poor". Results: Prostate Dose Gradient, Prostate Conformity and DIL Conformity indices had highlighted a major deviation from ideal scores. gUDI index classification showed most of the plans scored as "average" and "good". Conclusion: gUDI score can be a useful tool to quantify treatment plans quality also when volumes with different dose-prescription are treated.